Numerical FE Modeling and Design Methods of CCES Columns with Normal-Weight Crushed Dolomite Coarse Aggregate Fully Embedded IPE Steel-Section - Mostafa M. A. Mostafa (International Journal of Concrete Structures and Materials, 2024)
Abstract The composite concrete-encased steel (CCES) column member is made by the steel section embedded and covered in concrete from all sides. Due to the ability of the composite sections to bear heavy loads while using smaller sections, CCES columns have been widely used. Analytical studies on the CCES columns’ behavior using crushed dolomite coarse aggregate (CDCA) with different shear connectors (SCs) types/shapes and sizes under axial loads are described here. This study also aims to evaluate the current design methods to determine the ultimate capacity of the CCES with CDCA concrete columns using nine available codes. The results show that the finite element (FE) analysis could accurately predict the ultimate capacity of the CCES columns; the column’s capacity improved by about 41.75% as f cu increased by 60%. Increasing the IPE-shaped steel strength (f ss ) strategy is not very effective and gives brittle behavior even though enhancing the f ss improves the capacity. The column's capacity increased as the tie stirrups and steel bars ratios increased. The column’s capacity increased by about 17.63%, as steel bars ratios increased by 155.49%. The efficiency factors increased slightly as tie stirrups were raised but slightly decreased as steel bar ratios increased. Using the SCs system increases the columns’ capacity by an average value of about 4.9% of the specimen without SCs. The computed capacities using the nine available codes are conservative and safe. The closest estimates made by the YB9082-06 code are 26% less on average than the test results; in contrast, the safest predictions made by the ECP-LRFD code are 68% less, on average, than test results. Graphical Abstract